Pengaruh Media Jembatan Pelangi terhadap Perkembangan Aspek Kognitif Anak Usia Dini - Istiqamah, A. Mulkaida; Patiung, Dahlia; Rusdi, M.; U, M. Shabir; Damopolii, Muljono (Al Asma: Journal of Islamic Education, 2023)
Rainbow bridge media is a learning media that presents educators' messages in pictures, letters, and numbers, which can help students develop their cognitive aspects. This research aims to determine whether the use of Rainbow Bridge media affects the development of cognitive aspects of early childhood. This research is experimental research with a pretest-posttest design. The population in this study were all students at Nurul Taqwa Tokombeng Kindergarten and Al-Ikhlas Kindergarten, with a total of 45 students. The sample was 13 class B students at Nurul Taqwa Tokombeng Kindergarten and 13 class B students at Al-Ikhlas Kindergarten. The instruments used were observation sheets on cognitive aspects of children aged 5-6 years and observation sheets of rainbow bridge media. The analysis techniques used are descriptive statistical analysis and inferential statistical analysis. The research results show that using rainbow bridge media influences the development of students' cognitive aspects.